Safety of Exercise Testing in the Clinical Chinese Population - Dun, Yaoshan; Olson, Thomas P.; Ripley-Gonzalez, Jeffrey W.; Xie, Kangling; Zhang, Wenliang; Cai, Ying; Liu, Yuan; Shen, Yanan; Zhou, Nanjiang; Gong, Xun; Liu, Suixin (Frontiers in Cardiovascular Medicine, 2021)
This eighteen-year cross-sectional study was conducted to provide data on the safety of exercise testing in the clinical Chinese population. We retrospectively identified exercise tests completed at Xiangya Hospital of Central South University from January 1st, 2002 to December 31st, 2019. From 43,130 unique individuals (50.9% female), a total of consecutive 50,142 tests (standard exercise testing 29,466; cardiopulmonary exercise testing 20,696) were retrieved. Demographics, patients’ medical history and exercise testing characteristics, and exercise testing-related adverse events were described. Safety data is expressed as the number of adverse events per 10, 000 tests with a 95% confidence interval. The average patients’ age was 51 ± 13. The majority of patients were diagnosed with at least one disease (N = 44,941, 89.6%). Tests were maximal or symptom-limited. Common clinical symptoms included dizziness (6,822, 13.6%), chest pain or distress (2,760, 5.5%), and musculoskeletal limitations (2,507, 5.0%). Out of 50,142 tests, three adverse events occurred including; one sustained ventricular tachycardia, one sinus arrest with junctional escape rhythm at a rate of 28 bpm, and one syncopal event with fecal and urinary incontinence. The rate of adverse events was 0.8 events per 10,000 tests (95% confidence interval, 0.2-3.0) in men, 0.4 per 10,000 tests (0.7-2.2) in women, and 0.6 per 10,000 tests (0.2-1.8) total. This study represents the largest dataset analysis of exercise testing in the clinical Chinese population. Our results demonstrate clinical exercise testing is safe and the low rate of adverse events related to exercise testing might be due to the overall changes in clinical practice over time.